THE NEXUS BETWEEN CRITICISMS AND ETHICAL ISSUES IN ADVERTISING PRACTICE (Journal of the Management Sciences, 2025)
The Study sought to find out ethical issues in advertising, and the nexus between criticism and ethical issues in advertising practice. Social responsibility theory, AIDA Model and Persuasion theory formed the theoretical review. Library research method was used to gather data for this study. Findings revealed that, false advertising, deceptive advertising, comparative advertising, endorsements and testimonials and children advertising, were some of the ethical issues that confront advertising practice. Finding revealed that, when an advertisement is targeted at children in an unfair or deceptive manner or in a way that takes advantage of the children’s credulity such advertisement is unethical. It was also discovered that stereotype in advertising does not depict reality, and that it can make someone to pick one thing over the other. It was discovered that people criticise advertising as a result of unethical issues in advertising. Advertising fatigue also accounts for criticisms of advertising. Related empirical studies were reviewed. It was concluded that, for advertisement to be devoid of unethical issues, advertisers, advertising media and advertising agencies must endeavour to adhere to the code of ethics and code of conducts. It was recommended that, to ensure best practices and maintain high level of professionalism, the advertiser, advertising media and advertising agencies must always play by the rules, as enshrined in the codes of ethics and conducts.
Keywords: Advertising; Ethical issues; Criticism; Advertising practice